Empowering Novice Teachers through Mentorship and Supported Teaching in Schools: Implications for Education Policy and Practice - Ampomah, Robert; Manu, Jacob; Akyina, Kwadwo Oteng (Journal of Education and Practice, 2024)
Purpose: This study aimed to support novice teachers in teacher education institutions in Ghana on how mentoring and supported teaching in schools (STS) can be used to shape the novice teacher’s thought on the school profile dimension throughout the mentoring relationship. The purpose is to review literature on mentoring using Hudson's five factor mentoring model process and STS and think through how mentoring and STS can be improved in teacher preparation. The Hudson's five factor model of mentoring was used as the conceptual framework. Methodology: The study was conducted using document analysis (secondary data sources), such as reports, online papers, or datasets that have already been gathered from Google, ERIC, Research gate, and Academia. Findings: The findings of the study were that the STS has created an opportunity for mentors to spend time with their mentees and share their professional and pedagogical experiences. Again, it is believed that structured mentoring, feedback and reflection would enhance the student teacher’s capacity to succeed. Unique Contribution to Theory, Practice and Policy: The study suggests that there should be on-going professional development for mentors, structured mentoring programmes, feedback and reflection mechanisms to check for coherence through assessment procedures and monitor students’ progress. Case study research can also serve to illuminate both positive and problematic aspects of the STS mentoring.